2014
DOI: 10.1039/c4tb00563e
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanomaterials as new tools for immunotherapeutic applications

Abstract: Carbon-based nanomaterials, including carbon nanotubes and graphene, have gained great attention in the scientific community due to their unique physico-chemical properties, which could be also promising in many biomedical-related fields. In particular, their low cytotoxicity, achieved when properly functionalized, along with the possibility to link multiple bioactive molecules, realistically allows envisaging their potential use as a therapeutic platform. In this context, the immune system and immune response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…1 Carbon nanomaterials, such as carbon nanotubes (CNTs), graphene and carbon nanohorns (CNHs), have been studied for biomedical applications because of their unique characteristics. [2][3][4][5][6][7][8][9][10][11] Carbon nanomaterials are promising candidates for bone tissue engineering applications due to their superior cytocompatible, mechanical and electrical properties. [12][13][14][15][16][17][18] Some years ago, we initiated to explore study the applications of carbon nanomaterials for bone tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…1 Carbon nanomaterials, such as carbon nanotubes (CNTs), graphene and carbon nanohorns (CNHs), have been studied for biomedical applications because of their unique characteristics. [2][3][4][5][6][7][8][9][10][11] Carbon nanomaterials are promising candidates for bone tissue engineering applications due to their superior cytocompatible, mechanical and electrical properties. [12][13][14][15][16][17][18] Some years ago, we initiated to explore study the applications of carbon nanomaterials for bone tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…However, one first main issue encountered with these carbon‐based materials is their long dimensions (several tens of microns scale length) which may display similar toxicity to asbestos and thus requires procedures to shorten their dimensions. To solve this problem, CNTs have been treated in a strong oxidizing media under ultrasound to decrease their length and thus their length/diameter ratio . Furthermore, in the last decade, graphene has emerged as an exciting new material.…”
Section: From Nanoparticles and Polymers As Building Blocks To Smart mentioning
confidence: 99%
“…Also very promising is the presentation of biologically active peptides on inert surfaces, such as carbon nanomaterials, metals, and metal‐oxide‐based nanomaterials . In particular, carbon nanomaterials, including carbon nanotubes (CNTs) and graphene, have attracted great attention for their unique physicochemical properties that can be exploited in many biomedical areas.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of this kind of nanomaterial stems from its immunological inertness and, in particular, lack of immunogenicity . These pioneering findings prompted many research groups to further explore CNTs for immunotherapeutic applications . In the field of immunomodulation, a few studies have reported the use of CNTs to modulate immune responses.…”
Section: Introductionmentioning
confidence: 99%